P1466SYSTEMATIC LITERATURE REVIEW OF CLINICAL EVIDENCE FOR THE BODY COMPOSITION MONITOR IN DIALYSIS AND CKD. (6th June 2020) - Raddatz, Agnieszka; Moissl, Ulrich; Ray, Alistair; Eichinger, Christian; Wabel, Peter
Abstract: Background and Aims: The Body Composition Monitor (BCM) is a bioimpedance spectroscopy device to monitor the hydration status of dialysis and CKD patients. NICE (UK) reported only limited evidence on the clinical effectiveness in its Diagnostic Guidance 29. The aim of this work was to provide a structured review of the available evidence up to September 2018 grouped by the most important clinical outcomes (fluid overload, blood pressure, mortality and cardiovascular events). Method: MEDLINE, Embase and Cochrane databases were interrogated from 2006 to September 2018. Search and review of identified studies was conducted in compliance with the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Of 4497 articles identified, 843 were included for full-text review; 424 were full publications and were selected for further analysis. Eight randomized controlled trial (RCT) studies and 150 observational studies met the predefined inclusion criteria; of these, observational studies that recruited at least 100 patients and additionally reported important clinical outcomes such as mortality, cardiovascular (CV) events or hospitalization were selected. Two further RCTs were identified by supplementary searches, giving a total of 10 RCTs (total 2.156 patients) and 41 observational studies (total 168.453 patients) included in this review. The data was grouped by reported outcomes and for each outcome it was analyzed if an effect of BCM-monitored fluid management, or an association between BCM assessment and the respective outcome could be shown. A meta-analysis of the results was not conducted. Reduction of fluid overload: RCTs have shown that BCM-monitored fluid management and subsequent alteration of dialysis parameters can lead to effective reduction of fluid overload. Lowering of blood pressure: RCTs have indicated that BCM-monitored fluid management can effectively lower blood pressure. Impact on mortality / association with mortality: Multiple observational studies have shown a strong association between BCM measurements and mortality. One RCT demonstrated that mortality outcomes can be significantly improved in HD patients with BCM-guided fluid management, while two RCTs reported no significant difference in mortality outcomes. Impact on Cardio Vascular (CV) related events: Multiple observational studies have indicated that BCM measurements can predict CV events. One RCT indicated that CV events can be reduced by BCM-monitored fluid management, and two further RCTs indicated that using BCM guidance was at least as good as conventional fluid management. Conclusion: There is a strong body of evidence for various important outcomes covering a large patient basis - additional evidence is needed in well designed randomized controlled trials e.g. to demonstrate the effect of reducing BCM determined dehydration.